Constitutional Doctrine and the (Non)-Freedom of the Interpretation of the Constitution - Birmontienė, Toma (Vilnius University Open Series, 2024)
This article analyses the extent to which the Constitutional Court is free to develop the constitutional doctrine. As one of the preconditions for the formation of the constitutional doctrine, the freedom exercised by the Constitutional Court in interpreting the Constitution can be viewed as a subjective assessment of the provisions and principles of the Constitution by the justices of the Constitutional Court, which is determined by objective circumstances and is based on reasoning, in order to achieve the integrity of the Constitution, the balance of the values enshrined in it, and the viability of the legal basis of the life of society and the State. The limits to the freedom of the Constitutional Court in developing a new original constitutional doctrine (or a doctrine based on EU Law, international legal acts, or constitutional traditions of other democracies) remain a topical issue which raises debate not only on the content of such a doctrine, but also on the consistent continuity of the interpretation of the Constitution by the Constitutional Court, as the sole official interpreter of the provisions and principles of the Constitution.
Keywords: Constitutional Court; official interpretation of the Constitution; constitutional doctrine; development of the constitutional doctrine; reinterpretation of the constitutional doctrine